Strategi Media Relations Fraksi Partai Amanat Nasional dalam Meningkatkan Citra di Era Pemerintahan Presiden Prabowo Subianto - Fina Malika Azmi; Siska Yuningsih (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
This research explores the Media Relations strategies implemented by the Partai Amanat Nasional (PAN) faction in the context of political communication during the administration of President Prabowo Subianto. Building a positive image in politics through effective relationships with the mass media is essential. The purpose of this study is to identify the strategies employed by the PAN faction in managing relations, developing strategies, and expanding networks with the media. The public image of the PAN faction is shaped through media coverage. This research applies Media Relations strategy theory, which includes managing relationships, developing strategies, and network building, as well as image formation theory, which encompasses perception, cognition, motivation, and attitude. A qualitative method with a descriptive study approach was used, and data were collected through interviews and documentation. The findings reveal that 1.) The PAN faction actively engages in communication through media gatherings, press conferences, doorstop interviews, advertorial collaborations, and media involvement in discussions. 2.) The faction disseminates information using both conventional and digital media, emphasizing engagement and transparency. 3.) PAN also builds partnerships with external organizations through audience meetings, seminars, training, and discussions as efforts to expand its communication network. 4.) Supporting factors include the openness of the media team and the availability of communicative spokespersons, while obstacles arise from the rapidly changing dynamics of social media and limited control over external media content. 5.) The National Mandate Party faction builds its image through strategic and responsive communication across both digital and traditional media. However, challenges